The Role of Bilirubin and the Other “Yellow Players” in Neurodegenerative Diseases - Sri Jayanti; Libor Vítek; Claudio Tiribelli; Silvia Gazzin (Antioxidants, 2020)
Bilirubin is a yellow endogenous derivate of the heme catabolism. Since the 1980s, it has been recognized as one of the most potent antioxidants in nature, able to counteract 10,000× higher intracellular concentrations of H2O2. In the recent years, not only bilirubin, but also its precursor biliverdin, and the enzymes involved in their productions (namely heme oxygenase and biliverdin reductase; altogether the “yellow players”—YPs) have been recognized playing a protective role in diseases characterized by a chronic prooxidant status. Based on that, there is an ongoing effort in inducing their activity as a therapeutic option. Nevertheless, the understanding of their specific contributions to pathological conditions of the central nervous system (CNS) and their role in these diseases are limited. In this review, we will focus on the most recent evidence linking the role of the YPs specifically to neurodegenerative and neurological conditions. Both the protective, as well as potentially worsening effects of the YP’s activity will be discussed.